Relations Between Turkey and Russia in the Context of Energy Partnership - Yermekbayev, Adilbek; Khairullayeva, Venera; Iztayeva, Venera; Zhuztayeva, Bibazhar; Doszhanova, Akmaral (International Journal of Energy Economics and Policy, 2020)
This article discusses issues of modern cooperation between Turkey and Russia in the context of energy diplomacy. The article deals with the issues of formation, development of key moments and important aspects of changing the energy strategy of Turkey and Russia. The main factors contributing to the rapprochement of bilateral relations, including relations on several topical issues of international relations, are identified. The question of the interdependence of the two economies is the main point of this study. As a methodological basis of the study, the authors used the methods of comparative-political and system-functional analysis of international relations and the world economy. The issues of the influence of the interdependence of the economies of Russia and Turkey on the political dialogue between the two countries are considered. The key points in bilateral relations, the main risks, and threats are analyzed. The prospects for the further development of relations are also considered. As threats, the points related to the bloc unity of Turkey and NATO, the status of the Crimea, and questions about the Black Sea straits were highlighted. The current state of relations between Ankara and Moscow are mutually beneficial, but repeated asymmetry is not excluded. Keywords: Russia, Turkey, energy diplomacy, gas pipeline, Black Sea, security, foreign policy, cooperation JEL Classifications: F5, O3 DOI: https://doi.org/10.32479/ijeep.8448